Genetic Divergence and Isolation of the Green Sea Turtle (Chelonia mydas) in the Red Sea - K. Scott; S. He; R. S. Hardenstine; L. K. Tanabe; H. Barrios‐Garrido; M. P. Jensen; L. Afiq‐Rosli; N. E. Wildermann; C. M. Duarte; J. E. M. Cochran; M. L. Berumen (Ecology and Evolution)
ABSTRACT The green sea turtle Chelonia mydas is a wide‐ranging marine reptile, inhabiting all the world's tropical and warm‐temperate seas. This global distribution makes delineating population boundaries challenging, and molecular tools like genetic markers are often required to define these limits. The Red Sea hosts ~1500 nesting green turtles, but research in the region is limited. The Red Sea may foster genetically distinct populations due to geographic barriers and extreme environmental conditions, as observed in other Red Sea taxa. In the present study, we sampled 193 nesting females and hatchlings from five rookeries, which support ~550 nesting females per year, on the Saudi Arabian coast of the Red Sea. We aimed to determine the genetic diversity within the basin and connectivity around the Arabian Peninsula and to the wider Indian Ocean. We analysed 710 bp of the mtDNA d‐loop from five Red Sea rookeries. Five haplotypes, grouped into two highly divergent haplogroups, were identified. Haplogroup one comprised 85% of our sample library and four haplotypes (CmP71.1–CmP71.4), three of which were previously unreported, while haplogroup two was much less prevalent (15% of the sample library) and consisted of a single novel haplotype (CmP62.2) more closely related to Arabian Gulf haplotypes. Most Red Sea rookeries shared haplotypes, but we observed a slight north‐to‐south gradient due to the increasing prevalence of CmP62.2. Pairwise Fst differences showed high genetic differentiation between the Ras al Baridi and the Al Wejh rookeries, indicating restricted gene flow between two major nesting sites and highlighting the need for separate conservation management strategies within the basin. We suggest that the isolation of the Red Sea and past paleo and climatic events have led to the divergence of three endemic haplotypes and possibly an evolutionary adaptation to the elevated temperature within the basin, which warrants further study.